Evaluate 2 0 1 5 2 − 2 0 1 4 2 + 2 0 1 3 2 − 2 0 1 2 2 + . . . + 3 2 − 2 2 + 1 2 ( m o d 2 0 1 5 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First,notice that 2 0 1 5 2 ≡ 0 ( m o d 2 0 1 5 ) − ( 2 0 1 4 ) 2 ≡ − 1 ( m o d 2 0 1 5 ) , 1 2 ≡ 1 ( m o d 2 0 1 5 ) 2 0 1 3 2 ≡ 2 2 ≡ 4 ( m o d 2 0 1 5 ) , − ( 2 2 ) ≡ − 4 ( m o d 2 0 1 5 ) − ( 2 0 1 2 2 ) ≡ − 3 2 ≡ − 9 ( m o d 2 0 1 5 ) , 3 2 ≡ 9 ( m o d 2 0 1 5 ) . . . . − ( 1 0 0 8 2 ) ≡ − ( 1 0 0 7 ) 2 ( m o d 2 0 1 5 ) , 1 0 0 7 2 ≡ 1 0 0 7 2 ( m o d 2 0 1 5 ) .When we add all the above expressions we have 2 0 1 5 2 − 2 0 1 4 2 + 2 0 1 3 2 . . . . . . . . + 3 2 − 2 2 + 1 2 ≡ 0 ( m o d 2 0 1 5 ) .
a 2 − b 2 = ( a + b ) ( a − b ) . A bit of rearranging makes ( a + b ) = 2 0 1 5 :D
Problem Loading...
Note Loading...
Set Loading...
For any pair of numbers a and b we know that a 2 − b 2 = ( a + b ) ( a − b ) , so 2 0 1 5 2 − 2 0 1 4 2 = ( 2 0 1 5 + 2 0 1 4 ) ( 2 0 1 5 − 2 0 1 4 ) = ( 2 0 1 5 + 2 0 1 4 ) ( 1 ) = 2 0 1 5 + 2 0 1 4 . Repeat for 2013 and 2012, 2011 and 2010, etc, and you find that the sum of the sequence is the sum of every number from 1 to 2015. Apply Gauss' formula 2 n ( n + 1 ) and you find that the sum of the first 2015 numbers is 2 2 0 1 5 × 2 0 1 4 = 2 0 1 5 × 1 0 0 7 , which is obviously 0 ( m o d 2 0 1 5 ) .